A new pharmacological strategy against treatment-resistant depression - Pineda-Gomez, Juan Pedro; Millón-Peñuela, Carmelo; Cantero García, Noelia; Flores, Marta; Ladrón de Guevara-Miranda, David; Flores-Burgess, Antonio; Díaz-Cabiale, Zaida (Elsevier, 2024)
Major depressive disorder affects more than 50 million people in the world. However, 50% of patients don’t respond to two or more drugs or psychotherapeutic treatments, named treatment-resistant depression (TRD). In this work, we propose a new augmentation treatment against TRD based on combining Fluoxetine (FLX) and the N-terminal fragment Galanin, GAL(1–15). In Wistar Kyoto (WKY) rats, akin to endogenous depression geneti cally, we evaluate GAL(1–15)’s impact on FLX-induced behaviours on tests measuring despair and anhedonia. We explored GALR2 involvement using the antagonist M871 and an in vivo model with siRNA 5-HT1A knock down. Also, the 5-HT1AR was analyzed by autoradiography binding in several brain regions. We analyze the corticosterone levels and a dexamethasone-suppressed corticotropin-releasing hormone stimulation to study the HPA axis regulation. Our results shows that only the combination of FLX + GAL(1–15) induced antidepressant effects in the WKY animals in Behavioural tests related to despair. This combination also reduced corticosterone levels in the WKY animals and modulated the functional characteristics of the serotoninergic receptor 5-HT1A in the prefrontal cortex. These novel results suggest combining GAL(1–15) with FLX is a new potentiation strategy in TRD cases. It shows the innovative potential of the interactions between the galaninergic and serotonergic systems to find new strategies and drugs against resistant depression
Keywords: Fisiología; Depresión; Farmacología; Treatment-resistant depression; Pharmacotherapy; Fluoxetin; GAL(1–15)